Outcome of subtotal parathyroidectomy for surgical treatment of hyperparathyroidism after renal transplantation - Murilo Catafesta das Neves; Ana Beatriz Ribeiro Fonseca; Camila Akemi Yamashiro Koike; Davi Knoll Ribeiro; Mayra Messias Lera; Rodrigo Oliveira Santos (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: To evaluate the efficacy of STPX as a definitive treatment for Hyperparathyroidism after Renal Transplantation (HPT-RT) and determine whether there is a relationship between percentage intraoperative Parathyroid Hormone (ioPTH) decay levels and Parathyroid Hormone (PTH) values on the first postoperative day and surgical success. Methods: This retrospective study analyzed the medical records of prospectively followed patients diagnosed with HPT-RT submitted to STPX in two tertiary hospitals (Brazilian Unified Health System ‒ SUS) for two years. Patients were allocated in two groups according to operative success (SG ‒ normalization of ionized Calcium [iCa] and PTH six months after surgery) or operative failure (FG ‒ persistence of high iCa and PTH). The percentage ioPTH decay levels and the postoperative PTH absolute values on the first postoperative day were evaluated in both groups. Results: Of the total sample of 31 patients, surgical treatment was successful in 27 cases (87%). No statistically significant differences were observed between the groups for the percentage ioPTH decay levels (SG = 71.51% vs. FG = 70.4%), as well as for the PTH absolute values on the first postoperative day (SG = 52.69 pg/mL vs. FG = 54.55 pg/mL). Conclusion: Subtotal parathyroidectomy is an effective and safe procedure for treating HPT-RT; however, the use of PTH levels remains subjective and cannot be considered as a predictor of surgical success.